Firearm violence: a neglected "Global Health" issue - Meghan Werbick; Imran Bari; Nino Paichadze; Adnan A. Hyder (BMC, 2021)
Abstract Populations around the world are facing an increasing burden of firearm violence on mortality and disability. While firearm violence affects every country globally, the burden is significantly higher in many low- and middle-income countries. However, despite overwhelming statistics, there is a lack of research, reporting, and prioritization of firearm violence as a global public health issue, and when attention is given it is focused on high-income countries. This paper discusses the impact of firearm violence, the factors which shape such violence, and how it fits into global public health frameworks in order to illustrate how firearm violence is a global health issue which warrants evidence-based advocacy around the world.